An Efficient Tetraplex Surveillance Tool for Salmonid Pathogens - von Ammon, Ulla; Averink, Tessa; Kumanan, Karthiga; Brosnahan, Cara L.; Pochon, Xavier; Hutson, Kate S.; Symonds, Jane E. (Frontiers in Microbiology, 2022)
Fish disease surveillance methods can be complicated and time consuming, which limits their value for timely intervention strategies on aquaculture farms. Novel molecular-based assays using droplet digital Polymerase Chain Reaction (ddPCR) can produce immediate results and enable high sample throughput with the ability to multiplex several targets using different fluorescent dyes. A ddPCR tetraplex assay was developed for priority salmon diseases for farmers in New Zealand including New Zealand Rickettsia-like organism 1 (NZ-RLO1), NZ-RLO2, Tenacibaculum maritimum, and Yersinia ruckeri. The limit of detection in singleplex and tetraplex assays was reached for most targets at 10−9 ng/μl with, respectively, NZ-RLO1 = 0.931 and 0.14 copies/μl, NZ-RLO2 = 0.162 and 0.21 copies/μl, T. maritimum = 0.345 and 0.93 copies/μl, while the limit of detection for Y. ruckeri was 10−8 with 1.0 copies/μl and 0.7 copies/μl. While specificity of primers was demonstrated in previous studies, we detected cross-reactivity of T. maritimum with some strains of Tenacibaculum dicentrarchi and Y. ruckeri with Serratia liquefaciens, respectively. The tetraplex assay was applied as part of a commercial fish disease surveillance program in New Zealand for 1 year to demonstrate the applicability of tetraplex tools for the salmonid aquaculture industry.